2017
DOI: 10.1093/intqhc/mzx052
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the effectiveness of accreditation on hospital performance: A nationwide stepped-wedge study

Abstract: Hospital characteristics were not found to be predictors for the effects of accreditation, whereas conditions and types of care to some extent predicted the effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…A cross-sectional study using data from 4400 hospitals did not find differences in outcomes to be associated with type of accreditation programme. 90 Performance data from two cohort studies suggest that hospital size and type did not predict effects of accreditation 91 ; however, lower performing hospitals improved at a greater rate than moderate and higher performing hospitals. 92 Two case studies indicate that degree of improvement can depend on improvement capability of the inspected organisation, 43 and that accreditation can be easier to implement in smaller facilities.…”
Section: Resultsmentioning
confidence: 99%
“…A cross-sectional study using data from 4400 hospitals did not find differences in outcomes to be associated with type of accreditation programme. 90 Performance data from two cohort studies suggest that hospital size and type did not predict effects of accreditation 91 ; however, lower performing hospitals improved at a greater rate than moderate and higher performing hospitals. 92 Two case studies indicate that degree of improvement can depend on improvement capability of the inspected organisation, 43 and that accreditation can be easier to implement in smaller facilities.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, it is difficult to make a meaningful direct comparison with previous studies since to the best of our knowledge, there are no studies like our study which is (i) targeting AMI and stroke, (ii) comparing before and after accreditation, and (iii) using mortality as an outcome variable at the same time. This difficulty is even greater considering that the effect of accreditation can vary from disease to disease [ 27 ]. Nevertheless, a careful comparison of previous studies with our findings was performed as follows.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Devkaran S. et al’s studies which have used interrupted time series analysis to see if there were significant differences in the clinical quality measures before and after accreditation for all diseases reported that the structure and process quality indicators improved after accreditation compared to before, but the patient mortality reduction was not significant [ 31 , 32 ]. Given that the effect of accreditation on the mortality reduction can be disease-specific [ 27 ], it is natural that these studies targeting all diseases did not clearly demonstrate the effect of accreditation on patient mortality reduction. In addition to these, the results of other studies using mortality as an outcome indicator reported results in which accreditation had little or no effect on mortality reduction [ 16 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“… Brubakk et al (2015) claim that accreditation has little effect on patient outcomes, organizational culture, and reliability. Many other researchers argue that there was no convincing evidence on improving output quality and patient safety due to accreditation and certification ( Grepperud, 2015 ; Bogh, et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%